Therapeutic (Sub)stance: Current practice and therapeutic conduct in preparatory sessions in substance-assisted psychotherapy—A systematized review - Thal, Sascha B; Wieberneit, Michelle; Sharbanee, Jason; Skeffington, Petra M; Baker, Paris; Bruno, Raimondo; Wenge, Tobias; Bright, Stephen J (SAGE, 2022)
Background: Clinical trials are currently investigating the potential of substance-assisted psychotherapy (SAPT) as treatment for several psychiatric conditions. The potential therapeutic effects of SAPT may be influenced by contextual factors including preparation prior to and integration after the substance-assisted therapy sessions. Aims: This systematized review outlines recommendations for current practice in preparatory sessions in SAPT including safety measures and screening procedures, preparation of set and setting, session contents, methods, and roles, prerequisites, and appropriate conduct of therapists. Methods: A systematized review of the literature was conducted based on PRISMA guidelines. MEDLINE (OVID), PsycINFO (OVID), and Cochrane Library were searched and clinical trials, treatment manuals, study protocols, case studies, qualitative studies, descriptive studies, theoretical papers, reviews, book chapters, and conference proceedings published until February 1, 2022 were retrieved. Results: The final synthesis included k = 83 sources. Information about safety measures including screening of participants, set and setting, contextual-, physiological-, and psychological preparation, roles, competencies, prerequisites, and characteristics of the therapists, and the establishment of a therapeutic relationship were summarized and discussed. Conclusion: It is concluded that there is a consensus in the literature about the importance of adequate preparation before the administration of psychoactive substances in SAPT. However, the extent and approaches for these sessions vary across different models and there is a need for timelier and more rigorous qualitative and quantitative investigations assessing different approaches and techniques for the optimal preparation of clients in SAPT.